Design and analysis of mechanisms : a planar approach - Rider, Michael J., author (West Sussex, United Kingdom : Wiley, 2015)
A planar or two-dimensional (2D) mechanism is the combination of two or more machine elements that are designed to convey a force or motion across parallel planes. For any mechanical engineer, young or old, an understanding of planar mechanism design is fundamental.
Michael J. Rider - Faculty - Mechanical Engineering
Includes bibliographical references (page 306) and index
In English text.
Keywords: Gearing; Mechanical movements